ANALISIS DAMPAK PEMASARAN MEDIA SOSIAL TERHADAP MINAT BELI LAYANAN DISNEY+ HOTSTAR DI KOTA BANDUNG - Fida Fadhilah; Imanuddin Hasbi (POLITEKNIK LP3I JAKARTA, 2023)
One of the developments that have emerged in the 21st century is development of the digital age with internet use. Internet users in Indonesia experienced a significant increase in the era of Covid-19 pandemic period. One the increasing use of the internet in Indonesia is dominated using social media which is a way of getting information from text or picture of information that is given. Other than that, social media marketing also used by businesspeople to introduce their brands to a potential consumer. One of the business companies that uses social media to introduce their products is Disney+ Hotstar. The purpose of this research is to tell the effect of Social Media Marketing on Purchase Intention on Disney+ Hotstar Services in Bandung. This study uses quantitative with descriptive analysis, and population used in this research is Bandung city residents who used social media and known or used Disney+ Hotstar services. The sampling technique used was snowball sampling with 100 respondents. Using simple linear regression data analysis method with SPSS 27 for MAC. From the social media marketing hypothesis on purchase intention, the result is what it has a t-count value of 7,935 > t table value of 1,660 also a sig value of 0,000<0,05 which means a relevant impact on purchase intention. And the result of the social media marketing determination coefficient test on purchase intention is 39,1%.Keywords: Purchase Intention, Social Media Marketing